2019
DOI: 10.48550/arxiv.1907.05415
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning to learn with quantum neural networks via classical neural networks

Abstract: Quantum Neural Networks (QNNs) are a promising variational learning paradigm with applications to near-term quantum processors, however they still face some significant challenges. One such challenge is finding good parameter initialization heuristics that ensure rapid and consistent convergence to local minima of the parameterized quantum circuit landscape. In this work, we train classical neural networks to assist in the quantum learning process, also know as meta-learning, to rapidly find approximate optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
163
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(164 citation statements)
references
References 50 publications
0
163
1
Order By: Relevance
“…Consequently, although we can prove the absence of barren plateaus for general tensor-network based learning models with local losses, training them may still be infeasible when scaling up due to the intrinsic difficulty in computing the derivatives. We mention that a variety of strategies, such as specific parameter initialization [80] and pre-training [108], have been proposed to escape barren plateaus for variational quantum circuits. These strategies may also apply for tensor-network based learning and a further investigation along this line is highly desirable.…”
mentioning
confidence: 99%
“…Consequently, although we can prove the absence of barren plateaus for general tensor-network based learning models with local losses, training them may still be infeasible when scaling up due to the intrinsic difficulty in computing the derivatives. We mention that a variety of strategies, such as specific parameter initialization [80] and pre-training [108], have been proposed to escape barren plateaus for variational quantum circuits. These strategies may also apply for tensor-network based learning and a further investigation along this line is highly desirable.…”
mentioning
confidence: 99%
“…In Ref. [75], the idea of pretraining is introduced, i.e., the parameters are pretrained by classical neural networks, which are then transferred to the quantum neural network and fine tuned. In this way, the total number of optimization iterations required to reach a given accuracy can be significantly improved.…”
Section: Algorithm Design For Mitigating Barren-plateau Effectsmentioning
confidence: 99%
“…It has been shown that metalearned optimization outperforms generic hand-designed competitors in many tasks [29]. The application of this concept to the quantum domain has been recently considered in the context of the variational quantum algorithms [33,34].…”
Section: Classical Simulatormentioning
confidence: 99%
“…It is also possible to use derivativefree methods, such as Bayesian optimization for the same task [16]. Meta-learning can again be used in this context to develop task-specific optimizers [33,40]. In this approach, it is only necessary to have gradient information during the training.…”
Section: Classical Simulatormentioning
confidence: 99%